Relationship between Troponin Elevation, Cardiovascular History and Adverse Events in Patients with acute exacerbation of COPD. (3rd September 2015) - Campo, Gianluca; Pavasini, Rita; Malagù, Michele; Punzetti, Silvia; Napoli, Nicola; Guerzoni, Franco; Papi, Alberto; Ceconi, Claudio; Contoli, Marco
ABSTRACT: Evidence suggests that troponin (Tn) elevation during acute exacerbation of chronic obstructive pulmonary disease (AECOPD) may predict an increase in mortality risk. We performed an observational study of 935 patients admitted to hospital for AECOPD from January 2010 to December 2012. Principal clinical and laboratory data were recorded, especially ischemic heart disease (IHD) history, Tn T values and cardiovascular drug prescription. The occurrence of all-cause death, cardiac death (CD), nonfatal myocardial infarction (MI), heart failure and cerebrovascular accident (CVA) was assessed on December 2013. Overall, 694 patients respected inclusion and exclusion criteria. We identified 210 (30%) patients without Tn elevation (negative Tn T group) and 484 (70%) patients with Tn elevation (positive Tn T group). With the exception of CVA, all adverse events were significantly higher in positive Tn T group as compared to negative Tn T group. At multivariable analysis, positive Tn T failed to predict all-cause death. Contrarily, positive Tn T emerged as independent predictors of CD (HR 1.61, 95%CI 1.2–2.2, p = 0.04), nonfatal MI (HR 3.12, 95%CI 1.4–8.1, p = 0.03) and composite endpoint including CD and nonfatal MI (HR 1.73, 95%CI 1.2–2.7, p = 0.03). Of note, positive Tn T stratified prognosis in patients without IHD history, but not in those with IHD history. In conclusion, after hospital admission for AECOPD, we observed a significant increase in the risk of cardiac adverse events in patients with Tn T elevation, especially in those without IHD history.